Successful Bosutinib Experience in an Elderly Acute Lymphoblastic Leukemia Patient with Suspected Central Nervous System Involvement Transformed from Chronic Myeloid Leukemia - Atilla, Erden; Ataca, Pinar; Ozyurek, Elif; Erden, Ilhan; Gurman, Gunhan (Case Reports in Hematology, 2015)
Managing the blast phase in chronic myeloid leukemia (CML) is challenging because limited data are available for elderly patients. The involvement of the central nervous system (CNS) increases the risk of a poor prognosis. Here, we present an elderly blast phase CML patient with suspected CNS involvement who was successfully treated with bosutinib.